Differences in impact of Aboriginal and Torres Strait Islander status on cancer stage and survival by level of socio-economic disadvantage and remoteness of residence—A population-based cohort study in Australia. (April 2016) - Tervonen, Hanna E.; Aranda, Sanchia; Roder, David; Walton, Richard; Baker, Deborah; You, Hui; Currow, David
Highlights: Aboriginal people showed a pattern of more advanced stage and increased risk of cancer death compared with non-Aboriginal people. This pattern was detected irrespective of socio-economic disadvantage or remoteness. All areas appear to require attention in endeavours to improve cancer survival outcomes for Aboriginal people. Abstract: Background: Aboriginal and Torres Strait Islander people (referred to in this paper as "Aboriginal people") generally have lower cancer survivals and more advanced stages at diagnosis than non-Aboriginal people. There is conflicting evidence on whether these disparities vary by socio-economic disadvantage and geographic remoteness. This study examines variations in these disparities in New South Wales (NSW), Australia. Methods: Data for cancers diagnosed in 2000–2008 were extracted from the NSW Cancer Registry ( n  = 264, 219). Missing Aboriginal status (13.3%) was multiply imputed. Logistic regression and competing risk regression models were used to examine likelihood of advanced summary stage and risk of cancer death among Aboriginal compared with non-Aboriginal people by socio-economic disadvantage (categorised into quintiles 1: least disadvantaged—5: most disadvantaged) and remoteness. Results: Aboriginal people showed a general pattern of more advanced stage at diagnosis compared with non-Aboriginal people across socio-economic disadvantage and remoteness categories. After adjusting for demographic factors, year of diagnosis, summary stage and cancer site, Aboriginal people living outside the least disadvantaged areas had an increased risk of cancer death compared with non-Aboriginal people living in similar areas (sub-hazard ratio SHR 1.41, 95% confidence interval CI 1.09–1.81; SHR 1.59, 95%CI 1.31–1.93; SHR 1.42, 95%CI 1.22–1.64 and SHR 1.34, 95%CI 1.22–1.48 for quintiles 2–5, respectively). Compared with non-Aboriginal people, Aboriginal people had an elevation in the risk of cancer death irrespective of the remoteness, with the most pronounced elevations detected in remote/very remote areas (SHR 1.56, 95%CI 1.10–2.21). Conclusion: Compared with non-Aboriginal people, Aboriginal people had a higher risk of cancer death and higher likelihood of more advanced stage across socio-economic disadvantage and remoteness categories. All areas appear to require attention in endeavours to improve cancer survival outcomes for Aboriginal people.